Uji Toksisitas Subkronis Ekstrak Etanol Tali Putri (Cassytha filiformis L.) Terhadap Fungsi Ginjal Tikus - Yori Yuliandra; Armenia Armenia; Annisa Nur Salasa; Friardi Ismed (Jurnal Sains Farmasi & Klinis, 2015)
Sub-chronic toxicity test of the deffated ethanolic extract of  tali putri (Cassytha filiformis L.) on the rat renal function has been carried out. A number of 16 male rats aged 2-3 months, weighing ±250 g were used as experimental animals. The rats were divided into 4 groups which consisted of 1 control group and 3 extract-treated groups given 1.25, 2.5, and 5 mg/kg extract administrated intraperitoneally once a day for 14 days. The creatinine clearance, renal function, and the ratio of renal were calculated and analyzed by two-way ANOVA followed by Duncan’s test. The study showed that the creatinine clearance and renal function decreased significantly during treatment (p<0.05). The kidney weight ratio of groups treated with extract, especially with greater doses, showed a very significant increase as compared with control (p<0,01). These indicated that the ethanolic extract of  C. filiformis on the doses of 1.25 – 5 mg/kg might decrease the renal function, althought it seemed to be relatively safe when used for 14 days.